Bacteremia during neutropenic episodes in children undergoing hematopoietic stem cell transplantation with ciprofloxacin and penicillin prophylaxis - Worawut Choeyprasert (2018)
© 2016, The Japanese Society of Hematology. Bacteremia during neutropenic episodes is a cause of morbidity and mortality in patients undergoing hematopoietic stem cell transplantation (HSCT). We have used oral ciprofloxacin and penicillin V, from the start of the conditioning regimen until engraftment, for the prophylaxis of bacterial infection. The objective of this study was to retrospectively analyze the prevalence of and risk factors for breakthrough bacteremia during neutropenic episodes in autologous and allogeneic HSCT patients. There were 215 patients enrolled, with a median age of 8.32 years (range 0.51–21.64 years) between 2002 and 2014. The common underlying diseases were thalassemia and acute leukemia. Bacteremia was documented in 33 patients (15.3 %), with 39 microorganisms isolated. Escherichia coli (28.2 %) and Streptococcus viridans (12.8 %) were the most commonly isolated Gram-negative and Gram-positive bacteria, respectively. Multidrug resistant strains were found in 32 and 14.3 % of Gram-negative and Gram-positive bacteria, respectively. Risk factors for bacteremia were receiving anti-thymocyte globulin (ATG) [odds ratio (OR) 2.44, 95 % confidence interval (CI) 1.06–5.65, P = 0.037] and umbilical cord blood as a stem cell graft (OR 6.60, 95 % CI 1.04–41.83, P = 0.045). In conclusion, the prevalence of bacteremia was 15.3 % and the use of ATG and cord blood were risk factors for bacteremia during neutropenic episodes.